1991
DOI: 10.1002/j.2161-1912.1991.tb00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Advising of International Students

Abstract: The international student population in the United States has experienced phenomenal growth over the last three decades. During the 1957-1958 academic year, there were merely 43,39 1 international students on American college campuses. Today, a little more than 30 years later, the international student population exceeds 349,609 on these campuses (Zikopoulos, 1987). A number of factors have no doubt driven increasing numbers of students from all over the world to seek an education in the United States. Chief a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…As mentioned earlier, Japanese teachers are highly responsible for quality involvement in both intellectual and emotional student development (White, 1989). Therefore, Japanese (and other students with similar educational backgrounds) tend to be more dependent--or even demandingunder the assumption that professors should show, tell, or do for them that for which they would be expected to assume individual responsibility in American culture (Charles & Stewart, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, Japanese teachers are highly responsible for quality involvement in both intellectual and emotional student development (White, 1989). Therefore, Japanese (and other students with similar educational backgrounds) tend to be more dependent--or even demandingunder the assumption that professors should show, tell, or do for them that for which they would be expected to assume individual responsibility in American culture (Charles & Stewart, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advising international students could be challenging because of cultural differences, insufficient English language capabilities, and educational system differences (Charles & Stewart, 1991;Curtin et al, 2013;Kim, 2007;Offstein et al, 2004). In advising relations, deficiency in linguistic capabilities limits exchange of ideas with the advisor and puts the advisee in need of much handholding from the advisor in the writing stage.…”
Section: Student Factorsmentioning
confidence: 99%
“…In many cultures, especially from Asia, teachers are parental figures, and students from those cultures expect parent-like engagement from their American advisors (Charles & Stewart, 1991;Dong, 1996;Kim, 2007). The relationship has been perceived to be less personal in the US and most US faculty do not offer assistance or go out of their way to help a student (Eland, 2001).…”
Section: Student Factorsmentioning
confidence: 99%
“…The literature indicates that international students perceive academic advising as an important benefit and believe it exerts positive influences on their adjustment and academic performance (Cadieux & Wehrly, 1986;Charles & Stewart, 1991). For instance, Ku, Lahman, Yeh, and Cheng (2008) found that international doctoral students considered support from academic advisors a key factor for their well-being and academic success.…”
Section: International Students' Experiences With Academic Advisingmentioning
confidence: 99%